2017
DOI: 10.1007/s10661-017-6130-0
|View full text |Cite
|
Sign up to set email alerts
|

A large-scale investigation of the quality of groundwater in six major districts of Central India during the 2010–2011 sampling campaign

Abstract: This paper investigates the groundwater quality in six major districts of Madhya Pradesh in central India, namely, Balaghat, Chhindwara, Dhar, Jhabua, Mandla, and Seoni during the 2010-2011 sampling campaign, and discusses improvements made in the supplied water quality between the years 2011 and 2017. Groundwater is the main source of water for a combined rural population of over 7 million in these districts. Its contamination could have a huge impact on public health. We analyzed the data collected from a la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…According to a national drinking water quality survey in Bangladesh, the average concentrations of iron in drinking water reached 2.22 mg/L 29 . On the other hand, the average iron level in drinking well water in India has been shown to be 2.2 mg/L 32 with a maximum concentration of 51 mg/L 33 . Iron levels ranging from 0.15 to 25 mg/L in well water in the western area of the USA were also reported 34 .…”
Section: Discussionmentioning
confidence: 99%
“…According to a national drinking water quality survey in Bangladesh, the average concentrations of iron in drinking water reached 2.22 mg/L 29 . On the other hand, the average iron level in drinking well water in India has been shown to be 2.2 mg/L 32 with a maximum concentration of 51 mg/L 33 . Iron levels ranging from 0.15 to 25 mg/L in well water in the western area of the USA were also reported 34 .…”
Section: Discussionmentioning
confidence: 99%
“…The responsible for health surveillance actions were professionals linked to public health departments (40; 81.63%) from municipal, state, or federal spheres [31][32][33][34][35][36][37][38][39][40]42,43,[46][47][48][49][50][51][53][54][55][56][57][58][59][60][61][62][63]65,[67][68][69][70][71][72][73][74][75][76], agencies responsible for water protection [45,77], department of environment and conservation [41], department of public health engineering [78], national water laboratory [30], or in-field sanitary inspectors of the water test laboratory [52]. Sometimes, the surveillance involved other sectors besides health (e.g., environmental, civil protection, and responsible for the supply)…”
Section: Characterization Of Included Studiesmentioning
confidence: 99%
“…A study identified the relevance of the Jupiter database, which is an open-access database that centralizes the register of chemical analyses and allows the assessment of drinking water using a spatial-temporal categorization despite the high heterogeneity of sampling frequencies and type of pesticide analyzed may be a limiting factor [84]. The surveillance actions of water quality highlighted in this class addressed the identification of chemical contaminants in households (i.e., lead [71,73], arsenic [67,72,73], iron [71,73,78], nitrate [69,73,78], fluoride [47,78], aluminum, manganese, strontium, and nitrogen [73]), revealed locations that did not fully comply with regulations of chemical contamination [49], and identified volatile organic compounds within the allowed level [69]. Identifying these contaminants has been part of testing programs at residences of people from risk groups (e.g., women with children [71], low-income families with pregnant women, and young children [73]) and assessments of supply sources and sources needing treatment after a disaster [51].…”
Section: Class 2 -Analysis Of Physical-chemical and Microbiological P...mentioning
confidence: 99%
See 1 more Smart Citation
“…Those responsible for health surveillance actions were professionals linked to public health departments (40; 81.63%) from municipal, state, or federal spheres [30][31][32][33][34][35][36][37][38][39]41,42,[45][46][47][48][49][50][52][53][54][55][56][57][58][59][60][61][62]64,[66][67][68][69][70][71][72][73][74][75]; agencies responsible for water protection [44,76]; departments of environment and conservation [40]; departments of public health engineering [77]; national water laboratories [29]; or in-field sanitary inspectors of a water test laboratory [51]. Sometimes, the surveillance involved other sectors besides health (e.g., environmental, civil protection, and agencies responsible for the su...…”
Section: Characterization Of Included Studiesmentioning
confidence: 99%